Analisis Penerapan Good Corporate Governance (GCG) Dalam Sudut Pandang Ghulul Dan Risywah Sebagai Upaya Pencegahan Tindak Korupsi - Mohammad Rifqy Tiyantono; Lukman Hakim; Mohamad Djasuli (CV. ITTC INDONESIA, 2022)
Corruption is nothing new in Indonesia, since corruption instances appear to have grown ingrained in the culture. Diverse approaches and efforts have been made to remove corruption-related crimes in Indonesia, however these efforts have not proven fruitful. the utmost. In Islamic criminal law, corruption is closely related to embezzlement (ghulul) and bribery (risywah), each of which carries distinct legal penalties. Corruption occurred as a result of various factors, including a materialistic way of life, the political system, poor leadership, little religious and ethical education, the social structure, and corrupting laws. A framework called Good Corporate Governance (GCG) is required to minimize unethical business practices. Good Corporate Governance (GCG) is a movement of Ijtihad under Islamic law. As part of the larger endeavor to combat corruption in this country, religious nuances may be used to eradicate corruption through the usage and growth of legal discourse.